English for nursing : Vocational English course book. - Symonds, Maria Spada (Pearson Education Limited, 2012)
The Pearson Vocational English series meets the English language needs of learners in a range of specialisations. English for Nursing combines a strong grammar syllabus with the specialist vocabulary students need to succeed in this area. It contains topics that reflect the latest developments in the field making it immediately relevant to students’ needs. Each title contains a CD-ROM with interactive glossaries in both British and American English and the complete course book audio in MP3 format. Level 1: CEF level A1 to A2